Five‐year clinical performance of two fluoride‐releasing giomer resin materials in occlusal restorations. Issue 8 (7th August 2022) - Ozer, Fusun; Patel, Rishi; Yip, Jacqueline; Yakymiv, Oksana; Saleh, Najeed; Blatz, Markus B.
Abstract: Objective: To evaluate and compare the clinical performance of two nano‐hybrid giomer restorative composite materials after 5 years. Materials and Methods: Forty‐four pairs of restorations (total n  = 88) of a flowable giomer (Beautifil Flow Plus F00; Shofu Inc., Kyoto, Japan) and a conventional nano‐hybrid giomer restorative material (Beautifil II; Shofu Inc.) were placed in Class I cavities after the application of a dentin adhesive (FL‐Bond II; Shofu Inc.) and a flowable liner (Beautifil Flow Plus F03; Shofu Inc). After 5 years, 32 pairs of restorations were assessed using the modified United States Public Health Service criteria. Both tested materials were compared using Fisher's exact test and each tested clinical criterion for each material was analyzed separately with respect to different follow‐up periods using Friedman's test ( a  = 0.05). Results: None of the restorations showed complete retention loss, post‐operative sensitivity, secondary caries or color change. There were no significant changes to any of the clinical criteria for each material during the 5‐year evaluation period ( p  > 0.05) and no significant differences between the two materials in all clinical parameters after 5 years ( p  > 0.05). Conclusions: Five‐year clinical performance of both two nano‐hybrid giomer restorative materials was comparably acceptable and not significantly different for any of the parameters evaluated. Clinical Significance: Nano‐hybrid giomer‐based materials are clinically acceptable for the restoration of occlusal cavities as they demonstrate excellent performance after 5 years.